'I wouldn't be able to graduate if it wasn't for my mobile phone.' The affordances of mobile devices in the construction of complex academic texts. Issue 5 (3rd September 2018) - Barden, Owen; Bygroves, Mark
ABSTRACT: This is a case study of one student's mobile device use in HE. We draw on data generated by extended interviews to illustrate the learning practices and dispositions the student, now a co-author, evidenced with his smartphone and other devices whilst producing a third-year undergraduate assignment. We describe the process of assembling a complex academic text across multiple mobile internet-enabled devices. We aim to illuminate some contemporary mobile learning practices, and hence contribute to the discourse on pedagogy, assessment and mobile learning in HE. The paper is timely because although smartphones and internet access are near-ubiquitous in universities, there is relatively little extant research which reports in detail on the ways in which students actually use these technologies in their everyday learning and lives.